Ecotheology In Promoting Environmental Sustainability: Conserving The Eco-Friendly Islamic Doctrine In Jambi Province - Halim, Abdul; Rafii, Muhammad; Kusnadi, Edy (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2023)
Ecotheology is an important part of the modern century in the study of theology, the development of theological work is motivated by changes in human life in seeing things, such as the environment or nature. This paper seeks to sharpen eco-theological potential for environmental sustainability in Jambi province. Thus he encourages the preservation of eco-friendly Islamic doctrines through normative messages in addressing the position of nature for humans. This is emphasized in maintaining the environment as human attachment to nature, created in a balanced way, and the creation of nature for human life. This value is in line with the practice of the Jambi Malay Muslim community which has customary rules in maintaining the environment, land and forests. This spirit in customary law is a representation in the preservation of environmentally friendly Islamic teachings for the Jambi Malay Muslim community.